2015
DOI: 10.1186/s13584-015-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Israeli Druze women’s sex preferences when choosing obstetricians and gynecologists

Abstract: BackgroundConsideration and better understanding of patients’ needs on the part of the healthcare system might help increase the number of people seeking necessary medical care. Many studies have been conducted on patients’ preferences in choosing their health care provider, but the majority of them were conducted in modern western societies, establishing a need to explore other populations. The present study was performed in the Israeli Druze community which is composed of a uniquely traditional and religious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
49
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 24 publications
7
49
1
2
Order By: Relevance
“…This stressed the importance of female gynecologist or obstetrician at any health setting to enhance female to regularly visited health services. This consistent with Amir Alshiek et al, [24] who had reported that Nowhere is the gender of the health professional as crucial to the choice and adherence of young female as to the intimate nature of obstetrics / gynecology.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This stressed the importance of female gynecologist or obstetrician at any health setting to enhance female to regularly visited health services. This consistent with Amir Alshiek et al, [24] who had reported that Nowhere is the gender of the health professional as crucial to the choice and adherence of young female as to the intimate nature of obstetrics / gynecology.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore Arab female's preference for a female obstetrician/gynecologist in intimate procedures was due to feeling more comfortable with a female obstetrician/ gynecologist, [24,25]. Likewise, Rizk et al found that the reason given for same gender preference of religious was "embarrassment during intimate examinations" [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the more traditional and religious beliefs, the greater importance patients attached to the gender preference of their provider, due to modesty. This was previously verified by several gender preference studies that explored gender preference of religious and traditional women for their obstetrician/gynecologist physician (Amer-Alshiek et al, 2015;Amir, Hazan, Grutz, Amit, & Azem, 2012;Amir, Tibi, et al, 2012;Lafta, 2006;McLean et al, 2012;Rizk, El-Zubeir, Al-Dhaheri, Al-Mansouri, & Al-Jenaibi, 2005). The marital status of the responders might also link to a more modest behavior of married patients.…”
Section: Discussionmentioning
confidence: 66%
“…Female patients and study participants in LMICs often prefer female researchers over males due to cultural or religious reasons. 8,9 These studies help shape health care policies. Women researchers are also more likely to conduct research on women's health.…”
mentioning
confidence: 99%